Vanitas als Wiederholung - von Flemming, Victoria; Berger, Julia Catherine (De Gruyter, 2022)
Vanitas does not just address ephemerality but also the relationship of the self to history it negotiates identity and positions itself both self-critically and politically. In which contexts does contemporary culture take up this established motif of antiquity and the early modern period? Interdisciplinary considerations show how productive it can be to answer this question by reflecting on it in light of discussions about repetition.